2020
DOI: 10.1681/asn.2019080829
|View full text |Cite
|
Sign up to set email alerts
|

Apolipoprotein L1-Specific Antibodies Detect Endogenous APOL1 inside the Endoplasmic Reticulum and on the Plasma Membrane of Podocytes

Abstract: BackgroundAPOL1 is found in human kidney podocytes and endothelia. Variants G1 and G2 of the APOL1 gene account for the high frequency of nondiabetic CKD among African Americans. Proposed mechanisms of kidney podocyte cytotoxicity resulting from APOL1 variant overexpression implicate different subcellular compartments. It is unclear where endogenous podocyte APOL1 resides, because previous immunolocalization studies utilized overexpressed protein or commercially available antibodies that crossreact with APOL2.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
71
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 41 publications
(81 citation statements)
references
References 59 publications
10
71
0
Order By: Relevance
“…The work presented here and other published studies have shown significant similarities between humans [8][9][10]24] and transgenic mouse APOL1 expression patterns [17,18,24]. A reproducible and consistent observation from these combined studies is expression of APOL1 in podocytes and in endothelial cells of glomerular capillaries, peritubular capillaries, and larger blood vessels.…”
Section: Plos Onesupporting
confidence: 84%
See 2 more Smart Citations
“…The work presented here and other published studies have shown significant similarities between humans [8][9][10]24] and transgenic mouse APOL1 expression patterns [17,18,24]. A reproducible and consistent observation from these combined studies is expression of APOL1 in podocytes and in endothelial cells of glomerular capillaries, peritubular capillaries, and larger blood vessels.…”
Section: Plos Onesupporting
confidence: 84%
“…Although monoclonal antibodies would eliminate the variation inherent in polyclonal antibody production lots, the commercial monoclonal antibodies tested had significant non-specificity or poor sensitivity for APOL1. A recent report describing the development and validation of a large number of monoclonal antibodies against human APOL1 also did not identify proximal tubule staining in human kidney [ 24 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Scales emphasized the critical role of APOL1 haplotypes for G1-and G2-mediated cytotoxicity in cultured podocytes stably expressing APOL1 RVs. 49,50 Specifically, the podocytotoxicity was dependent on the African APOL1 haplotype (E150/I228/K255), not simply the specific RV, even though there were no differences in localization or expression level between haplotypes. 51 She demonstrated that critical thresholds of expression at the plasma membrane must be surpassed to achieve cytotoxicity.…”
Section: Apol1-induced Cell Injury In Mammalian Cellsmentioning
confidence: 97%
“…Furthermore, the administration of endoplasmic reticulum stress inhibitors to human podocytes in vitro was shown to be protective against cytoskeletal damage and cell death [53]. Although this hypothesis is compelling, however, a recent in vitro study of ApoL1 localization in podocytes using anti-ApoL1 antibodies was unable to find any ApoL1 localization in lipid droplets; further study is required to determine the in vivo localization pattern of ApoL1 and to resolve this apparent contradiction between study results [54].…”
Section: Loss Of G0 Protective Functionmentioning
confidence: 99%